2002
DOI: 10.1063/1.1485301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ga content on defect states in CuIn1−xGaxSe2 photovoltaic devices

Abstract: Defects in the band gap of CuIn1−xGaxSe2 have been characterized using transient photocapacitance spectroscopy. The measured spectra clearly show response from a band of defects centered around 0.8 eV from the valence band edge as well as an exponential distribution of band tail states. Despite Ga contents ranging from Ga/(In+Ga)=0.0 to 0.8, the defect bandwidth and its position relative to the valence band remain constant. This defect band may act as an important recombination center, contributing to the decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
107
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(124 citation statements)
references
References 11 publications
(11 reference statements)
16
107
0
Order By: Relevance
“…These results are consistent with computer modeling of devices, in which an increase in the band tail width greatly decreases overall efficiency. The measured band tail widths are in the same range as those measured on similar materials by transient photocapacitance spectroscopy [20]. The PL and PLE data suggest two possible connections between the performance of the devices and the PL and PLE data: (1) the abruptness of the PLE onset and (2) the separation of the band edge and the first PL emission not derived from a free-to-bound transition may relate to device performance.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…These results are consistent with computer modeling of devices, in which an increase in the band tail width greatly decreases overall efficiency. The measured band tail widths are in the same range as those measured on similar materials by transient photocapacitance spectroscopy [20]. The PL and PLE data suggest two possible connections between the performance of the devices and the PL and PLE data: (1) the abruptness of the PLE onset and (2) the separation of the band edge and the first PL emission not derived from a free-to-bound transition may relate to device performance.…”
Section: Resultssupporting
confidence: 54%
“…The band edge shape is typically thought to be determined by an exponentially decaying density of states that extends into the forbidden gap, the width of which has been connected to the degree of structural disorder in the crystal, including disorder that results from local composition fluctuations [19]. Such band tails are common in Cu-poor CIGS and have been measured by luminescence techniques as well as transient photocapacitance spectroscopy [6,20]. Band edge widths for the six samples in this study were directly measured by fitting PLE spectra with error functions and are shown in the last column of Table I.…”
Section: Resultsmentioning
confidence: 99%
“…The bandgap energies of the CIGS films with the GGI ratios of 0.18 and 0.25 were estimated around 1.11 eV and 1.14 eV, respectively [19]. Although typically the bandgap energies of around 1.4-1.5 eV, which could be achieved by further increasing the Ga contents for the CIGS films, are ideal for the photovoltaic devices under the solar spectrum of AM1.5G, the high Ga contents lead to the formation of the deep-level defects, degrading the performance of the CIGS solar cells [20]. From the aspects of compositions for the device-grade CIGS films, the CGI and GGI ratios of the as-prepared CIGS films were within the preferable ranges.…”
Section: Two-step Processmentioning
confidence: 99%
“…In general, FF gradually declines when the front or back side bandgap exceeds a certain value, as shown in Figures 3 and 5. The reduction of FF by the excessive front side bandgap is mainly attributed to the formation of the conduction band barrier obstructing electron collection, while the reduction by the excessive back side bandgap is because the defect traps become deeper as the bandgap increases with the Ga/(Ga + In) ratio [19,20]. Finally, based on the simulation results, we optimized the DGB structure for the CIGS solar cell incorporating the Cd-free ZnS buffer layer and fabricated the CIGS cells with a size of approximately 0.25 cm 2 .…”
Section: Resultsmentioning
confidence: 99%